Da crítica à religião à teoria do fetichismo em Marx - Noronha, Vitor César Zille (2017)
Would it be possible to synthesize the marxian critique of religion into the famous assertion in which the author relates religion to opium? Either proponents or opponents would say yes. To investigate the theoretical and philosophical basis of this hegemonic reading, we will need to return to Hegel, since to Marx religion is what Hegel understands as it. Thus, the true religion lays the political ethics foundation of the true State. This divine-made State to Hegel is exactly what is opposed by Marx mostly from Feuerbach’s ideas. Subsequently, we will present a original marxian critique of religion from his primary bibliography, his elaborations, his continuities and discontinuities through his intellectual trajectory. We intend to consider his dialogs, approximations, distances and overcomings in relation to Hegel and Feuerbach, the two greatest sources of the marxian thought on the religious phenomenon. At last, we will penetrate meticulously in the theory of fetishism in Marx, presenting it as the Holy Trinity of Mammon (commodity, money and capital), the proposal of a dialectical inversion from the Hegelian category of the Holy Trinity. The critique of religion takes a fundamental step and becomes the negative momentum to the theory of fetishism. Something epistemologically and onthologically new arises. The fetishism is the corecategory to understand the capitalism as religion, it is the mediation between real life and the religious reflection that occurs through value (in the three functional forms, commodity, money and capital), subject of social relations. In addition, we will elaborate a critique to Marx since he did not applied his universal-particular dialectic to religion, as he did to philosophy and politics, for example, remaining still tributary to a hegelian identified thought, which means a deep logicalmethodological problem inside Marx’s thought. Eventhough he could capture the dialectical aspects of religion - protest and legitimation, at the same time – he abandons his logical coherence of dialectical unity between theory and practice. Marx doesn’t esteem properly the utopic potential of religion and the concrete possibility of a antifetishist religion.